Experimental System Level Platform for B3G Scenarios - Monteiro, Valdemar (2010)
This paper provides a complete specification of the packet based cellular wireless system level simulator that addresses a beyond 3G scenario involving heterogeneous wireless systems interconnected via an IP backbone network. Important aspects as the Link layer design (including the MAC layer) are specified, as well as the C++ object oriented simulation architecture. Since the IP level and the physical layer aspects should be avoided, interfaces representing these layers are proposed for different type of radio access systems. The concept is showcased by a multi-RAT system composed of HSDPA and a Wi-Fi system using load balancing techniques.